2002
DOI: 10.1016/s0378-1135(02)00015-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of concurrent infections with Pasteurella multocida and Ascaridia galli on free range chickens

Abstract: Pasteurella multocida and Ascaridia galli are observed with high prevalences in free range chickens in Denmark, but the impact is unknown. A study was carried out to examine the interaction between A. galli and P. multocida in chickens and the impact on production.Five groups, each with 20 18-week-old Lohmann Brown chickens were infected. Group 1 was orally infected with 1000 AE 50 embryonated A. galli eggs. Group 2 received 10 4 cfu P. multocida intratracheally. Group 3 was infected with A. galli and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 18 publications
0
51
0
1
Order By: Relevance
“…Following the same theme, the effect of A .galli on subsequent pasteurella multocida infections was shown to be predominantly on weight gain and egg production (Dahl et al 2002). These studies indicate that interactions between parasitic, bacterial and viral diseases exist.…”
Section: Pathogenesis and Clinical Symptomsmentioning
confidence: 72%
“…Following the same theme, the effect of A .galli on subsequent pasteurella multocida infections was shown to be predominantly on weight gain and egg production (Dahl et al 2002). These studies indicate that interactions between parasitic, bacterial and viral diseases exist.…”
Section: Pathogenesis and Clinical Symptomsmentioning
confidence: 72%
“…Heavy infection with adult worm can cause obstruction of the small intestine and death (Ackert and Herrick 1928;Ikeme 1971;Tugwell and Ackert 1952). A. galli may also transmits other infection such as Salmonella in chicken (Chadfield et al 2001;Eigaard et al 2006) and concurrent infection of A. galli with other pathogens produce more severe pathological condition than the single infection with this pathogen alone (Dahl et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that older fowls can harbour high burdens of parasites without clinical signs, but act as reservoir of these parasites to the young ones as they feed together (Dahl et al, 2002).…”
Section: Prevalence and Intensity Of Gastro-intestinal Infection In Mueamentioning
confidence: 99%